implify:

2x + 6y - xy when x=5 and y=3

*
12
41
3
13

1 answer

To simplify the expression 2x + 6y - xy when x = 5 and y = 3, we substitute the given values into the expression:

2(5) + 6(3) - 5(3)

Solve the multiplication first:

10 + 18 - 15

Then perform the addition and subtraction:

28 - 15

The simplified expression is:

13
Similar Questions
  1. implify4√5-√13+√5
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 3 answers
more similar questions